Metabolic Syndrome, Chronic Kidney Disease, and Cardiovascular Disease: A Dynamic and Life-Threatening Triad - Mário Raimundo; José António Lopes (Cardiology Research and Practice)
The metabolic syndrome (MS) and chronic kidney disease (CKD) have both become global public health problems, with increasing social and economic impact due to their high prevalence and remarkable impact on morbidity and mortality. The causality between MS and CKD, and its clinical implications, still does remain not completely understood. Moreover, prophylactic and therapeutic interventions do need to be properly investigated in this field. Herein, we critically review the existing clinical evidence that associates MS with renal disease and cardiovascular disease, as well as the associated pathophysiologic mechanisms and actual treatment options.